Thermoxylanolytic and Thermosaccharolytic Potential of a Heat Adapted Bacterial Consortium Developed From Goat Rumen Contents - Lepcha, Khusboo; Basak, Arijita; Kanoo, Subham; Sharma, Prayatna; BK, Puja; Ghosh, Shilpi (Frontiers in Energy Research, 2021)
Thermoactive xylanases have important applications in the industrial deconstruction of lignocellulosic plant biomass, due to their sustained activity even at high temperature conditions of industrial bioreactors. We herein report the development of a thermoactive xylanolytic microbial consortium from the semi-digested contents of goat rumen and characterization of the xylanolytic enzyme cocktail produced by it.The consortium exhibited maximum endoxylanase activity at pH6 and at 60°C. Zymogram analysis revealed the production of multiple xylanases. The xylanase cocktail was stable over a pH range of 5 to 9 and it retained 74% activity after pre-incubation (60°C) for 50min. It's activity was enhanced in presence of β-mercaptoethanol, NH4+, Mg²⁺ and Ca²⁺, whereas Hg²⁺ had an inhibitory effect. The xylanolytic cocktail was further utilized for the saccharification of alkali pre-treated rice straw and mushroom spent rice straw. Saccharification was studied quantitatively using the dinitrosalicylic acid method and qualitatively using scanning electron microscopy. Results indicated the potential of the xylanolytic cocktail for the saccharification of rice straw and highlighted the significance of chemical and/or biological pre-treatment in improving the accessibility of the substrate towards the xylanase cocktail.